PENGEMBANGAN E- LKPD BERBASIS KOMIK PADA TEMA 8 SUBTEMA 3 USAHA PELESTARIAN LINGKUNGAN PEMBELAJARAN 2 - Khoerunnissa, Mutiara; Kurnia, Dadang; Siti Sundari, Fitri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of the research is to develop and determine the feasibility of comic-based E-LKPD in Science subjects in Theme 8 Subtheme 3 Efforts to Preserve the Learning Environment 2, where E-LKPD as a teaching material contains materials, summaries, and concise instructions, in the implementation refers to the achievement of basic competencies can be accessed through electronic media on various platforms. The research method used is Research and Development (R&D), with the ADDIE model (analysis, Design, Development, Implementation, Evaluation). The research was carried out in the even semester of 2023/2024 at Leweungkolot 07 State Elementary School, Bogor Regency, consisting of 25 students in class V. Interview, questionnaire, and documentation data analysis techniques The results of the validation trial of media, material, and language experts stated that comic-based E-LKPD products were very feasible with an average score of 98%, while the results of the student trial stated that comic-based E-LKPD was in the very feasible category with an average score of 96%. Based on the results of the research, it can be concluded that comic-based E-LKPD is very feasible to be used in the learning process, especially in theme 8 subtheme 3 efforts to preserve the learning environment 2.